A futuristic vision of pocket ultrasound machines: watch this space. Issue 3 (August 2014) - Woo, Joyce Su Ling; Magotti, Robert; Benzie, Ronald
Abstract: Introduction : Australian medical ultrasound started in 1959 with the establishment of the Ultrasonics Institute. Since then the technology has advanced tremendously. We are now not only able to obtain clearer images on high specification ultrasound machines but also on pocket‐sized ultrasound machines that are compact, lightweight and affordable. Method : The following descriptive review will examine the indication for use of pocket ultrasound machines in different clinical settings as well as provide evidence of its image clarity and accuracy. Potentially eligible studies were sought primarily through searches of the electronic databases PubMed, Medline (1996–Present), Embase (1996–Present) and Cochrane Library. Conclusion : Pocket ultrasound machines, with appropriate ultrasound knowledge and training, can be incorporated successfully in patient management. The addition of point‐of‐care ultrasound has been shown to improve management recommendations and outcomes.